Use of Flexible Budgeting to Face Economic Uncertainty and a Changing Business Environment - Saifuddin; Ismatul Maula; Naila Farodysa; Syifa'ul Khairiyatil Ummah; Umami Hapsahwati (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2024)
Flexible fencing is an approach in financial planning and financial management designed to deal with economic competition and changing business environments. In a fast-changing and unstable business environment, traditional budgeting methods may be less effective because they tend to be rigid and difficult to adapt to unexpected changes. There are two ways to look at flexible budgets: through a corporate finance standpoint and a personal finance standpoint. From a company's financial point of view, a flexible budget is a budget plan that adjusts to changes in costs, volumes, and revenues. Simply put, how a company calculates how much budget it has, estimates how much it needs, and how many targets it wants to achieve. Meanwhile, from the point of view of personal finance, flexible budgeting is a method of financial budget planning that is prepared based on financial conditions, income, and expenses. Then adjust it according to changes in spending habits that occurred in the previous year. Usually personal budgets are adjusted in monthly periods when usually all kinds of billing cycles occur.